2D DOA estimation based on matrix method and joint diagonalization technique - Hai-qiang ZHANG; Wei-min SU; Hong GU; Xue-long HU (Tongxin xuebao)
When space phase factors are the same in one direction or two orthogonal directions,the convensional direction-of-arrival methods cannot estimate DOA effectly,resulting in performance degradation.Therefore,joint diagonalization technique was utilized to estimate two-dimensional (2D) DOA on the basis of DOA matrix method.This technique can not only achieve automatic pairing of estimated DOA,but also effectively resolve the performance degradation when the space phase factors are the same.The simulation results show the effectiveness of the technique.